Reflective bibliographic review: the psychic suffering of the hospitalized child (Research, Society and Development, 2021)
Childhood is a period of great psychosocial fragility, due to the occurrence of extensive physical, emotional and behavioral changes; and the routine imposed by hospitalization can exacerbate this vulnerability. The objective of this article is to carry out a reflexive bibliographic review, with a qualitative approach and descriptive character, about the psychological suffering of hospitalized children and the strategies used to alleviate it. Several studies were selected from journals indexed on the “Periódicos Eletrônicos de Psicologia” (PePSIC) portal, with the following keywords “hospital psychology”, “child” and “hospitalized”, in June 2019. After analysis, two relevant themes emerged: the importance of the health team in the child's psychosocial development and multiple aspects of the psychological monitoring of the hospitalized child. Finally, it was concluded that hospitalization can negatively influence children and that certain interventions can minimize psychological distress. It is expected that the results of this research to direct new research and stimulate the planning of effective interventions accordingly.